Desain Desain Antar Muka Pengguna Aplikasi Telemedicine: - - Windarti, Syamsu - (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2024)
During the COVID-19 pandemic, there was a trend of decreasing number of visits to 18 community health centers in Yogyakarta City. People are afraid to go to the community health center because they are afraid of being exposed to the Covid 19 virus. For this reason, facilities are needed that help people feel safe and protected from exposure to the Covid virus when checking their health condition. This facility is in the form of a system that makes it easier to consult and carry out examinations without having to come and meet with a doctor in person. One example of a system is a mobile-based system. This research aims to produce a user interface design for a teleconsultation application in prototype form by applying the Figma multimedia application program which is specifically for designing a prototype. The research was carried out using the literature study method and the observation method by observing teleconsultation applications that already exist in the Play Store/App Store. The design phase carried out starts from designing the initial prototype, dynamic prototype, and evaluating the results.This research produced several designs consisting of; (1) Patient interface prototype, (2) Doctor interface prototype, (3) Pharmacy interface prototype, and (4) Admin interface prototype. With this research, an online consultation system interface design has been produced which can be implemented in the form of an actual application so that it can help the public to carry out online consultations without having to meet face to face.